2020
DOI: 10.1021/acs.inorgchem.0c03088
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Reduction of Chelated Uranyl to Stable Tetravalent Uranium Coordination Complexes in Aqueous Solution

Abstract: The solution-state interactions between octadentate hydroxypyridinone (HOPO) and catecholamide (CAM) chelating ligands and uranium were investigated and characterized by UV− visible spectrophotometry and X-ray absorption spectroscopy (XAS), as well as electrochemically via spectroelectrochemistry (SEC) and cyclic voltammetry (CV) measurements. Depending on the selected chelator, we demonstrate the controlled ability to bind and stabilize U IV , generating with 3,4,3-LI(1,2-HOPO), a tetravalent uranium complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 55 publications
(135 reference statements)
1
15
0
Order By: Relevance
“…While research continues by others on developing treatments for internal radionuclide exposure [ 34 , 35 , 36 , 37 ], the results of this preliminary investigation showed that nutraceutical compounds could function as chelators for some metals considered internal radionuclide contamination hazards. Clearly, further research is required.…”
Section: Discussionmentioning
confidence: 98%
“…While research continues by others on developing treatments for internal radionuclide exposure [ 34 , 35 , 36 , 37 ], the results of this preliminary investigation showed that nutraceutical compounds could function as chelators for some metals considered internal radionuclide contamination hazards. Clearly, further research is required.…”
Section: Discussionmentioning
confidence: 98%
“…Since the significant mobility of uranyl (UO 2 2+ ) in environment can originate health risks derived from radiological contamination, complexation of U 4+ and U 6+ by L27 was recently analyzed by UV-spectrophotometry, XANES and EXAFS. It was found that L27 , as well as other spermine-derived analogues (e.g., L28 ), can stabilize U 4+, in aqueous media (inert complex towards oxidation/hydrolysis in acidic aqueous media) which is particularly relevant since tetravalent actinides are quite susceptible to hydrolysis even under very acidic conditions [ 74 ]. This study allows the further understanding of the conditions under which the uranium species are stable in solution, therefore contributing to preview the chemical behavior of radionuclides in diverse systems (chemical, biological or environmental).…”
Section: Poly-hydroxypyridinonesmentioning
confidence: 99%
“…The exaggerated stability and mobile nature of uranyl­(VI) UO 2 2+ ion makes it the most important uranium species that contaminates groundwater. To reduce the mobility of UO 2 2+ , it is usually reduced to insoluble uranium­(IV) species. , Recently, octadentate hydroxypyridinone, catecholamide chelating ligands, and uranium generated tetravalent uranium that is practically inert toward oxidation or hydrolysis in acidic and aqueous solutions . Adsorption of uranium species in different oxidation states of the metal ion was studied experimentally using mass spectrometry and theoretical calculations.…”
Section: Introductionmentioning
confidence: 99%